Investigation on firm efficiency: evidence from selected Asia-Pacific countries - Tan, Khar Mang; Kamarudin, Fakarudin; Amin Noordin, Bany-Ariffin; Abdul Rahim, Norhuda (Emerald, 2018)
Purpose–The purpose of this paper is to examine the firm efficiency or technical efficiency (TE),pure technical efficiency (PTE) and scale efficiency (SE) in the selected developed and developingAsia-Pacific countries.Design/methodology/approach–The sample consists of a sum of 700 firms in selected developed anddeveloping Asia-Pacific countries over the period from 2009 to 2015. The non-parametric data envelopmentanalysis under the production approach is used to investigate firm efficiency.Findings–On average, this paper discovers that the firms in selected Asia-Pacific countries are moderatelyefficient. Scale inefficiency (SIE) is found to be the dominant source of firms’technical inefficiency. Theanalysis of return to scale shows that the large firms tend to operate at decreasing return to scale level, whilethe small firms tend to operate at increasing return to scale level.Practical implications–The findings from this paper provide significant insights to the policy makers andfirm managers in promoting the efficient firms of Asia-Pacific countries.Originality/value–The present paper conducts a critical analysis on return to scale in the firms sector ofAsia-Pacific context, which is ignored by the past studies on firm efficiency since the analysis of return toscale is mostly emphasized on banking sector. The precise nature of SIE is important for a firm to be efficientin achieving the firm’s primary goals of profit maximization and sustaining market competitiveness.